Environmental & architectural phenomenology. Vol. 7, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1996)
Vol. 7, No. 3, Fall 1996 (includes “items of interest,” "citations received,” book review of Helmi Jarviluoma's Soundscapes: Essays on Vroom and Moo, and commentaries on Edward "Ted" Relph's Place and Placelessness).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals